To Study or to Sleep? The Academic Costs of Extra Studying at the Expense of Sleep. Issue 1 (20th August 2012) - Gillen‐O'Neel, Cari; Huynh, Virginia W.; Fuligni, Andrew J.
<x xml:space="preserve">Abstract</x> This longitudinal study examined how nightly variations in adolescents' study and sleep time are associated with academic problems on the following day. Participants (N = 535, 9th grade Mage = 14.88) completed daily diaries every day for 14 days in 9th, 10th, and 12th grades. Results suggest that regardless of how much a student generally studies each day, if that student sacrifices sleep time to study more than usual, he or she will have more trouble understanding material taught in class and be more likely to struggle on an assignment or test the following day. Because students are increasingly likely to sacrifice sleep time for studying in the latter years of high school, this negative dynamic becomes increasingly prevalent over time.